Clinical characteristics and management strategies in adult foreign-body airway obstruction: A retrospective cohort study - Hongzhen Yin; Tong Wang; Changshun Zhong; Yingya Cao; Xiaogan Jiang; Qiancheng Xu; Weihua Lu (PLoS ONE, 2026)
Airway foreign-body aspiration in adults is uncommon but can be life-threatening.Flexible bronchoscopy is the standard first-line therapy,but critically ill patients may need extracorporeal life support.This study aims to characterize the diagnosis,management,and outcomes of adult airway foreign-body cases treated at a single center over nearly 12 years to inform a standardized clinical pathway.A single-center retrospective observational study of consecutive patients aged ≥14 years with confirmed airway foreign body who were treated at a tertiary hospital in China were conducted.Medical records of consecutive adolescent and adult patients diagnosed with airway foreign-body aspiration and admitted to the hospital from 01/01/ 2014–30/11/2025 were reviewed.Data included demographics,imaging,extraction method, respiratory support and so on.Descriptive statistics were reported as medians with interquartile ranges or counts and percentages.A total of 41 patients were included,with a median age of 59.5 years(interquartile ranges 51–72) and 65.85% male.Flexible bronchoscopy was attempted as the primary intervention in 38 patients(92.68%) and succeeded in 81.58%(31/38) to remove airway foreign body.Most patients(78.05%) required only nasal cannula oxygen,while nine patients(21.95%) needed advanced support including mechanical ventilation (14.63%),high-flow oxygen(4.88%),and extracorporeal life support (2.44%).At discharge,most survivors had a good neurological outcome,with 36 patients(87.80%) having a Cerebral Performance Categories score of 1.The 28-day survival rate was 92.68%.These findings show that flexible bronchoscopy is an effective first-line therapy,and rigid bronchoscopy or surgery is useful when flexible bronchoscopy fails.In unstable cases,timely extracorporeal life support can bridge to definitive removal.These results support a tiered,multidisciplinary approach incorporating early chest computed tomography,flexible bronchoscopy,and escalation to advanced airway or extracorporeal support.